Tamadun Islam dan tamadun Melayu - Ab. Aziz Mohd. Zin 1949-; Abd. Wahid Jais; Abdullah Yusof; Abu Hassan Sham; Ahmad Hakami Khairuddin; Ahmad Zaki Berahim @ Ibrahim; Aizan Ali @ Mat Zin; Ali Mohammad; Faezah Kassim; Faisal @ Ahmad Faisal Abdul Hamid (Siri teks pengajian tinggi., 2006)
History and relations between Islamic civilization and Malay civilization in Malaysia.